REGULATORY FRAMEWORK FOR ISLAMIC BANKING IN TANZANIA (Jurnal Kemanusiaan, 2017)
ABSTRACT The growing trend of Islamic banking in East Africa is subsequent to the growth of Islamic banking in the world. Tanzania as one among East African countries is comprehended with the Islamic banking practices in an emerged stance. However, the absence of regulatory framework governing Islamic banking is believed to hinder its development. Moreover, the literature reveals the absence of global standards, regulatory, and supervisory framework dealing with Islamic banking. The paper narratively, analyses the significance of the sharia regulatory framework for Islamic banking by synchronising the authors’ view concerning Islamic banking regulations. Henceforth, a ground regulatory framework for Tanzanian context is proposed. Therefore, a confidence among players will be raised with standardised Islamic banking practices.